First UK patient cohort treated with stereotactic ablative radiotherapy for primary kidney cancer - Anjali Zarkar; Dan Henderson; Antony Carver; Geoff Heyes; Victoria Harrop; Sarah Tutill; Julie Kilkenny; Andrea Marshall; Nada Elbeltagi; Helen Howard (BJUI Compass, 2023)
Abstract Aims Stereotactic ablative radiotherapy (SABR) for primary renal cell carcinoma (RCC) is a promising non‐invasive ablative treatment option. A prospective interventional clinical trial published showed that treatment was feasible and well tolerated. We present the first single‐institution UK cohort of patients with primary RCC receiving protocol‐based SABR with prospective follow‐up. We also present a protocol that could be used to facilitate more widespread use of the treatment. Materials and methods Nineteen biopsy‐proven primary RCC patients were treated with either 42 Gy in three fractions on alternate days or 26 Gy in a single fraction based on predefined eligibility criteria using either Linear Accelerator or CyberKnife platform. Prospective toxicity data using CTCAE V4.0 and outcome data such as estimated glomerular filtration rate (eGFR) and tumour response using CT thorax, abdomen and pelvis (CT‐TAP) were collected at 6 weeks, 3, 6, 12, 18 and 24 months post treatment. Results The 19 patients had a median age of 76 years (interquartile range [IQR] 64–82 years) and 47.4% were males, and they had a median tumour size of 4.5 cm (IQR 3.8–5.2 cm). Single and fractionated treatment was well tolerated and there were no significant acute side effects. The mean drop from baseline in eGFR at 6 months was 5.4 ml/min and that at 12 months was 8.7 ml/min. The overall local control rate at both 6 and 12 months was 94.4%. Overall survival at 6 and 12 months was 94.7% and 78.3%, respectively. After a median follow‐up of 17 months, three patients experienced a Grade 3 toxicity, which was resolved with conservative management. Conclusion SABR for primary RCC is a safe and feasible treatment for medically unfit patients, which can be delivered in most UK cancer centres using standard Linear Accelerator as well as CyberKnife platforms.